О родстве московской и кирилло-белозерской редакций Стишного пролога - Чистякова, Марина Владимировна Владимировна (Slavistica Vilnensis, 2012)
В конце первой четверти XIV в. по инициативе сербской иерархии на Балканах началось введение Иерусалимского устава вместо Студийского. Разновидность Пролога с краткими стихами, связанная с Иерусалимским уставом, известна в двух переводах с греческого языка середины XIV в.: болгарском и сербском [Соболевский 1903, 5; Петков 2000, 20–21]. В южнославянской книжности был более распространен болгарский перевод Стишного (метрического) пролога, выполненный в тырновском книжном центре1 [Иванова 1979, 122]. Не ранее последней четверти XIV в. этот перевод проник к восточным славянам2. Версия прошла редактирование в Сербии или на Афоне, так как во всех восточнославянских списках, включая древнейший на осенне-зимние месяцы — Москва, Российская государственная библиотека (далее РГБ), ф. 304.I, № 720, 1429 г., — представлены жития Саввы (14.I) и Симеона (13.II) сербских и некоторые другие особенности, например, молитва о заступничестве за болгар и сербов в конце жития Ионна Рыльского (21.X), см. подробнее [Турилов 2010, 291]....Marina ChistiakovaOn the Relationship between the Kirillo-Belozersky and Moscow Editions of the Versed SynaxarionThe Versed Synaxarion of the Kirillo-Belozersky collection 1.1240, created in Rostov diocese in 1452 and preserved at the Russian National Library, is the oldest copy of the Kirillo-Belozersky edition of the Versed Synaxarion. The comparison of its structure with the Moscow edition of the Versed Synaxarion (Russian State library, Trinity Lavra of St. Sergius, no. 720, 721, 722) suggests there is a relationship between the two editions. Textual analysis was employed to reconstruct the common prototype of the two editions. The Tarnovo edition in this “proto-edition” has been supplemented with homilies for selected dates. These homilies are a common feature of the Kirillo-Belozersky and Moscow editions alone and are not commonly found in other Eastern Slavic editions of the Versed Synaxarion.Comparison of the structure of the Kirillo-Belozersky 1.1240 and the Moscow edition demonstrates that some texts in the copy 1.1240 have been either edited or deleted, and an additional comparison with the Simple Synaxarion has been made. The Moscow edition is less innovative and is not affected by these changes. Individual homilies in the Kirillo-Belozersky edition derive from the Alphabetical Jerusalem Paterikon, the Slavic Compilation Paterikon, and the Rome Paterikon as well as from some detailed versions of the lives of the saints; the Kirillo-Belozersky edition has little in common with the corpus of individual sermons of the Moscow edition, which includes the homilies of Isaac the Syrian, Nikita Stethatos, Ephrem the Syrian, Abba Dorotheus, and other authors.Keywords: Cyrillic manuscript tradition, calendar didactic miscellanea, Versed Synaxation, Kirillo-Belozersky and Moscow editions of the Synaxarion.